Money in the Middle East and North Africa : monetary policy frameworks and strategies - Cobham, David P.; Dibeh, Ghassan, 1963- (Routledge political economy of the Middle East and North Africa series ;, 2011)
Monetary policy in the Middle East and North African (MENA) countries remains an understudied area; this book fills an important gap by examining monetary policy frameworks and monetary policy strategies in the region. Building on the editors' earlier book, Monetary Policy and Central Banking in the Middle East and North Africa, which focused on central bank independence issues and on exchange rate regimes, this book emphasises monetary policy strategies. Part I contains an overview of the financial markets and institutions which condition the choice of monetary policy strategy in.